Mini-ALPPS-based multidisciplinary treatment leading to long-term survival in a patient with a large HCC: A case report - Liu, Gao-Min; Zhang, Yao-Min (Frontiers in Surgery, 2023)
Background: The future liver remnant (FLR) induced by stage I ALPPS in HCC might be limited due to liver fibrosis/cirrhosis or incomplete liver parenchymal transection. Case presentation: A 51-year-old male with hepatitis B liver fibrosis was diagnosed with a large HCC (13.5 x 12.5 x 13.8 cm). The FLR of the patient was insufficient to permit one-stage tumor resection. Therefore, the two-stage ALPPS surgery was planned. Stage I ALPPS was performed with incomplete liver parenchymal transection due to bleeding (the reason why we called it Mini-ALPPS). On postoperative day (POD) 18, CT revealed that the FLR hypertrophy was poor. The FLR/standard liver volume (SLV) had only increased from 22.00% to 34.63%. Salvage transhepatic arterial chemoembolization (TACE) was performed on POD 22 days to control possible tumor progression during the waiting period and to further facilitate FLR growth. Sixteen days later, CT reassessment of FLR revealed a 42.5% FLR/SLV. A right hepatectomy was then uneventfully performed. Although HCC recurred after 586 days, the patient survived for more than 1920 days after stage II ALPPS. DISCUSSION: Damage control during a difficult conventional Stage I ALPPS was important. TACE during the interstage and postoperative periods of this Mini-ALPPS was safe and beneficial. Mini-ALPPS-based multidisciplinary treatment could bring patients long-term survival. But Mini-ALPPS should not be selected as the primary solution for such patients today, as some other minimally invasive and effective strategies are available.